2017
DOI: 10.4236/ojgas.2017.71002
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Efficacy of Triple Therapy of Sofosbuvir, Pegylated INFalpha 2a and Ribavirin in Treatment of Chronic Hepatitis C Patients Genotype 4 with High Fibrosis

Abstract: Purpose: The aim is evaluation of the efficacy of triple therapy of sofosbuvir, pegylated INFalpha 2a and ribavirin in treatment of chronic hepatitis C (CHC) patients genotype 4 who have high fibrosis. Materials and Methods: Fifty HCV patients with high fibrosis (F3 & F4) were included in the study. Results: SVR rate was 54%; non-responders rate was 12% and relapsers rate was 34%. When comparing SVR between F3 group patients and F4 group, it was 88% and 66% respectively, which means that SVR was higher in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Nevertheless, the results obtained in our study were found to have a SVR rate higher than that obtained in a study done by Aboud et al in 2017 (54%) who evaluated the efficacy of triple therapy of sofosbuvir, ribavirin, and IFN in treatment of chronic HCV patients having fibrosis. This could be attributed to the fact that in Aboud study, all the patients chosen had high degree of fibrosis, while the patients in our study were mainly child A which could explain the higher SVR rate [19].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Nevertheless, the results obtained in our study were found to have a SVR rate higher than that obtained in a study done by Aboud et al in 2017 (54%) who evaluated the efficacy of triple therapy of sofosbuvir, ribavirin, and IFN in treatment of chronic HCV patients having fibrosis. This could be attributed to the fact that in Aboud study, all the patients chosen had high degree of fibrosis, while the patients in our study were mainly child A which could explain the higher SVR rate [19].…”
Section: Discussionmentioning
confidence: 71%
“…Considering group B, the SVR rates in our study (72%) were lower than that obtained by either Elmashad et al [15] (84%) or Dolatimehr et al [16] (88%) or Kowdley et al [17] (89%). This higher SVR12 could be due to the fact that the abovementioned studies included mainly genotype 1 patients; maybe if it included other genotypes, the results could have been different, as most of Egyptians are genotype 4 Omran et al [19,18] and Kouyoumjian et al in [5]. Nevertheless, the results obtained in our study were found to have a SVR rate higher than that obtained in a study done by Aboud et al in 2017 (54%) who evaluated the efficacy of triple therapy of sofosbuvir, ribavirin, and IFN in treatment of chronic HCV patients having fibrosis.…”
Section: Discussionmentioning
confidence: 98%